Input for the preparation of a regional agenda for the programme of action of the international conference on population and development : towards 2014 and beyond (UN ECLAC SantiagoCL, 2010)
Examines the pending issues for 2010 - 2014. Identifies the actions and priorities for closing the implementation gaps of the ICPD Programme of Action five years from the end of its formal implementation period by putting forward recommendations for tackling the issues and for following-up. Presents resources and options for designing a strategy to maximize the impact and fulfilment of the population agenda beyond 2014. Highlights some cross-cutting approaches for tackling the population and development issues in the region and outlines some the elements that should be taken into account when establishing agreements, goals, policies and mechanisms for following up the agenda.
Keywords: POPULATION PROGRAMMES